Putative Promoter Motif Analyses Reinforce the Evolutionary Relationships Among Faustoviruses, Kaumoebavirus, and Asfarvirus - Oliveira, Graziele P.; de Aquino, Isabella L. M.; Luiz, Ana P. M. F.; Abrahão, Jônatas S. (Frontiers in Microbiology, 2018)
Putative promoter motifs have been described in viruses belonging to the nucleocytoplasmic large DNA viruses (NCLDVs) group; however, few studies have been conducted to search for promoter sequences in newly discovered amoebal giant viruses. Faustovirus and kaumoebavirus are two Asfarviridae-related giant viruses belonging to the NCLDVs group. The phylogenetic relationships among these viruses led us to investigate if the promoter regions previously identified in the asfarvirus genome could be shared by its amoebal virus relatives. Previous studies demonstrated the role of A/T-rich motifs as promoters of asfarvirus. In this study, we reinforce the importance of A/T rich motifs in asfarvirus and show that the TATTT and TATATA motifs are also shared in abundance by faustovirus and kaumoebavirus. Here, we demonstrate that TATTT and TATATA are mostly present in faustovirus and kaumoebavirus genomic intergenic regions and that they are widely distributed at 0 to -100 bp upstream to the start codons. We observed that putative promoter motifs are present as one to dozens of repetitions in intergenic regions of faustovirus, kaumoebavirus and asfarvirus, which is similar to that described previously for marseilleviruses. Furthermore, the motifs were found in most of the upstream regions of the core genes of faustovirus, kaumoebavirus and asfarvirus, which suggests that the motifs could already be present in the ancestor of these viruses before the irradiation of this group. Our work provides an in-depth analysis of the putative promoter motifs present in asfarvirus, kaumoebavirus and faustovirus, which reinforces the relationship among these viruses.